PATU12 Acute central nervous system infections in adults—a retrospective cohort study in the NHS northwest region. Issue 11 (22nd October 2010) - Michael, B; Beeching, N J; Sidhu, M; Roberts, M; Bonington, A; Hart, I J; Kneen, R; Miller, A; Solomon, T; Stoeter, D
Abstract : Background: Over the last 15 years bacterial meningitis has received considerable attention; viral central nervous system (CNS) infections have been relatively neglected. Aim: Examine the relative incidence, clinical features and management of suspected adult CNS infections across the Region. Methods: Multicentre (10 hospitals) cross-sectional retrospective cohort study over 3 months. All patients with cerebrospinal fluid analysis or acyclovir and/or third-generation cephalosporin; those with clinical features suspicious of a CNS infection were included. Management was compared with the national meningitis and regional encephalitis guidelines. Results: 385 patients were screened; 217 had a suspected CNS infection; 44 (20%) had a CNS infection: 18 aseptic meningitis (one herpes simplex virus (HSV)-2), 13 purulent meningitis (four Streptococcus pneumoniae ), and 13 encephalitis (3 HSV-1). The median (range) time from admission to suspicion of CNS infection and to LP was longer for patients with encephalitis than meningitis (4 (0.3–312) vs 0.3 (0.1–12) h, p<0.001, and 23 (4–360) vs 12 (2–48) h, p=0.042, respectively); and median time to treatment was longer for acyclovir than cephalosporin (7 (0.5–312) vs 3 (0.3–312) h, p=0.002). Conclusions: Encephalitis was as common as purulent meningitis, and HSV as common as S pneumoniae . However, the management of patients with encephalitis was worse than meningitis. National encephalitis guidelines are needed.